Allyl isothiocyanate and 6-(methylsulfinyl) hexyl isothiocyanate contents vary among wild and cultivated wasabi (Eutrema japonium) - Yamane, Kyoko (Breeding science, 2023)
Copyright © 2023 by JAPANESE SOCIETY OF BREEDING.